The surgical management of hidradenitis suppurativa in the United Kingdom: a national survey of care pathways informing the THESEUS study. Issue 1 (January 2022) - Howes, Rachel; Ingram, John R; Thomas, Kim S; Collier, Fiona; Rodrigues, Jeremy N.; ,
Abstract: Background: The evidence-base underpinning treatment efficacy and effectiveness for hidradenitis suppurativa (HS) is limited, as has been highlighted in the wide-ranging research priorities established by a James Lind Alliance priority-setting partnership (PSP). Understanding the landscape of surgical practice is a key step towards tackling undesired variation in care and resolving treatment uncertainties. This survey of current surgical practice aimed to describe care pathways involving surgeons for the management of HS and surgical approaches to management. Methods: In the development of the prospective cohort Treatment of Hidradenitis Suppurativa Evaluation Study (THESEUS), a bespoke electronic surgeon survey was conducted to describe variation in care pathways and surgical preferences in the management of HS. This was disseminated to a pre-defined denominator list of surgeons using local collaborators through the reconstructive surgery trials network (RSTN). Results: Key results were small numbers of surgeons working in formal multidisciplinary teams (MDTs) (8/198, 4%), heterogeneity of first-line intervention, low rates of guideline endorsed treatments (laser and deroofing in particular), variation in wound closure methods and follow-up length, and that over half of respondents do not use well-validated outcome instruments to determine treatment success/failure (110/198, 56%). Conclusions: This survey demonstrated variation in care, which is likely to be undesirable. Surgeons treating HS patients might consider developing MDTs or referring patients to those with an interest in HS and considering routine outcome measurement. Such steps might reduce variation, increase standardisation of care and improve access to specific treatments.